Experimental listeriosis: A study of purinergic and cholinergic inflammatory pathway - Jaguezeski A.M.* (2020)
© 2019 Elsevier B.V.The cholinergic, purinergic and oxidative stress systems were related to nervous system damage in some pathologies, as well as being involved in pro-inflammatory and anti-inflammatory pathways. The objective was to investigate changes in purinergic, cholinergic systems and oxidative stress related to the neuropathology of listeriosis. Gerbils were used as experimental models. The animals were divided in two groups: control and infected. The animals were orally infected with 5 × 108 CFU/animal of the pathogenic strain of Listeria monocytogenes. Collected of material was 6 and 12th days post-infection (PI). Infected animals showed moderate mixed inflammatory infiltrates in the liver. The spleen and brain was used for PCR analyses, confirming infection by L. monocytogenes. Increase in number of total leukocytes because of an increase in lymphocytes in infected (P < 0.001). ATP and ADP hydrolysis by NTPDase was lower at 6 and 12th days PI in infected animals than in the control group. ADA (adenosine deaminase) activity was higher on the 6th day PI (P < 0.05) and decreased on the 12th day PI (P < 0.05) in infected animals. AChE (acetylcholinesterase) activity did not differ between groups on the 6th day PI; however, activity decreased in infected group on the 12th day PI (P < 0.05). On the 12th day PI, an increase of oxygen-reactive species levels and lower catalase and superoxide dismutase activities in the infected group was observed, characterizing a situation of cerebral oxidative stress. The inflammatory and oxidative mechanisms are present in listeriosis in asymptomatic animals, and that ectonucleotidases and cholinesterase's are involved in immunomodulation.